SUPPLY CHAIN AND LOGISTICS: A KEY TO EXECUTING INDUSTRIALISED BUILDING SYSTEM (IBS) IN MALAYSIA - Rohaida, Affandi; Abdul Kadir, Marsono; Izni Syahrizal, Ibrahim; Masine, Md Tap; Aliff Ridzuan, Bunawan (i-CATS University College Publication, 2024)
Industrialised building system (IBS) has become a priority in modern construction methods, enhancing building components ’ quality, speeding up completion time , and reducing construction costs. The building components are manufactured off-site and later assembled on the project site. Therefore, the efficiency of logistics is a crucial element in the supply chain process to ensure the efficient movement of components and information to fulfil demands. This paper discusses how several companies from Japan, the United Kingdom, and Italy successfully improved their process of construction prefabrication components through the adaptation of an efficient and effective supply chain and logistics management concept. Results showed that the lean construction principle was opted for their supply chain and logistics. The element of lean principlse such as just-in -time, kanban, continual improvement (kaizen and last planner), and coordination among both upstream supplier s and downstream customers have initiate d successful improvements in their productivity. These successful concepts can be considered in maximising the full potential of an IBS supply chain and logistics management in the future.